Development of a Science Process Skills (SPS) test for assessing environmental chemistry concept: Salt hydrolysis in grade XI - Sari, Eka Puspita Kartika; Muntholib, Muntholib; Nihayah, Umi Husnun (Education and Development Research, 2025)
Science process skills (SPS) are fundamental to inquiry-based science learning and important for linking chemistry concepts with environmental issues. However, valid instruments to assess SPS in specific topics, such as salt hydrolysis, are still limited. This study aimed to develop and validate a multiple-choice test to evaluate eleventh-grade students’ SPS in the context of salt hydrolysis, emphasizing environmental chemistry applications. A research and development (R&D) design with five stages was employed: literature review, item development, expert validation, pilot testing, and finalization. Four chemistry education specialists provided expert judgment, and a pilot study was conducted with 150 eleventh-grade students from five high schools. Item validity, difficulty, discrimination index, and reliability were analyzed. The final test contained 28 items with a high content validity index (CVI = 0.90). Item analysis indicated two easy, 25 medium, and one difficult item. Discrimination indices classified five items as very good, 20 good, two sufficient, and one poor. All items were empirically valid, and the reliability coefficient (Cronbach’s alpha = 0.891) demonstrated strong internal consistency. Compared with similar SPS instruments, this test integrated authentic environmental contexts, such as the impact of salt hydrolysis on water pH, thereby enhancing ecological validity. The instrument provides teachers with a reliable diagnostic tool to identify students’ strengths and weaknesses in SPS. Beyond assessment, the instrument supports formative and summative evaluations, integrates environmental issues into chemistry learning, and serves as a reference for developing similar instruments in other science domains.